A review of advances in the understanding of lupus nephritis pathogenesis as a basis for emerging therapies [version 1; peer review: 2 approved] - Susan Yung; Desmond YH Yap; Tak Mao Chan (F1000Research, 2020)
Lupus nephritis is an important cause of both acute kidney injury and chronic kidney disease that can result in end-stage renal disease. Its pathogenic mechanisms are characterized by aberrant activation of both innate and adaptive immune responses, dysregulation of inflammatory signaling pathways, and increased cytokine production. Treatment of lupus nephritis remains a challenging issue in the management of systemic lupus erythematosus since the clinical presentation, response to treatment, and prognosis all vary considerably between patients and are influenced by ethnicity, gender, the degree of chronic kidney damage, pharmacogenomics, and non-immunological modulating factors. Elucidation of the various immunopathogenic pathways in lupus nephritis has resulted in the development of novel therapies, including biologics that target specific antigens on B lymphocytes to achieve B cell depletion, agents that modulate B cell proliferation and development, drugs that block co-stimulatory pathways, drugs that target T lymphocytes primarily, and therapies that target complement activation, signaling pathways, pro-inflammatory cytokines, and neutrophil extracellular traps. This review will discuss recent advances in the understanding of disease pathogenesis in lupus nephritis in the context of potential emerging therapies.